Design and characterization of a gene-encoding DNA nanoparticle in a cell-free transcription-translation system - Galvan, Angelica Rose; Green, Christopher M.; Hooe, Shelby L.; Oktay, Esra; Thakur, Meghna; Díaz, Sebastián A.; Veneziano, Remi; Medintz, Igor L.; Mathur, Divita (ACS applied nano materials, 2024)
DNA nanotechnology has made initial progress toward developing gene-encoded DNA origami nanoparticles (NPs) that display potential utility for future gene therapy applications. However, due to the challenges involved with gene delivery into cells including transport through the membrane, intracellular targeting, and inherent expression of nucleases along with interference from other active proteins, it can be difficult to more directly study the effect of DNA NP design on subsequent gene expression. In this work, we demonstrate an approach for studying the expression of gene-encoding DNA origami NPs without the use of cells. We utilize a pure E. coli-derived cell-free transcription-translation (TXTL) system, which is composed of optimized components from bacterial expression, for benchtop studies to assess how the promoter sequence in conjunction with structural design of the DNA NP template affects gene expression. The gene for an optimized Renilla luciferase was first amplified into a single-stranded (ss) scaffold strand and then folded into a 12-helix bundle DNA NP with exogenous staple strands as a test platform. Using luciferase-based bioluminescence assays to characterize the relative protein expression level, it was found that the gene can still be transcribed when folded, albeit at a lower rate than the double-stranded DNA gene segment. On comparing three variants of DNA NP with different promoter configurations, results indicate that a promoter designed to remain in ssDNA form has reduced protein expression from the DNA NP, and replacing the promoter sequence with an arbitrary sequence significantly lowers protein expression. This work demonstrates the power inherent in cell-free TXTL systems as an aid to study the gene expression capabilities of DNA NPs toward design and development of future applications.